Delegation of Authority for Secondary Education Management Aspects of Regional Assets / Property at the East Java Provincial Education Office - Siswoko Andianto; Widyawati Boediningsih (Faculty of Law, Merdeka University Surabaya, 2021)
After the enactment of the Law 23/2014 as the new regional government law (UU Pemda), the government formulates new regulations related to changes in the concurrent division of government affairs between the central government and regional governments. The purpose of this study is to describe the implementation of the transfer of authority to manage secondary education from the point of view of the aspect of management of regional assets / assets in the East Java provincial education office and the problems in the transfer of authority to manage secondary education from the point of view of the aspect of managing regional assets / property in the provincial education office. East Java. Nornative empirical research methods. Basically, it is an amalgamation of a normative legal approach with the addition of various empirical elements. The result of the research is that the Field Verifier Team and the Regional Assistance Team have a central role in overcoming problems related to the transition in the Secondary Education sector, namely by re-correcting the results of data collection and confirming the results of data collection both to the Surabaya City education office concerned and to the Education Office. East Java Province. All local governments, both provincial and district / city, must implement this policy. One of the regions that has also implemented this policy is the Province of East Java. The East Java Provincial Government has specifically implemented the policy of transferring secondary education management as mandated by Law no. 23 of 2014 through the East Java Provincial Education Office.